(untitled) (Olhar de Professor, 2020)
The article deals with the profile of higher education teachers in Brazil, in terms of performance and training. In the 2000s there was a significant expansion of higher education, with an increase in the number of institutions and courses, but the number of teachers did not follow the same pace of growth, producing an overload of activities for teachers. There was an uneven increase in the number of enrollments in relation to the number of teachers. Working conditions became more precarious and, with the advancement of neoliberal policies of individual accountability of the subjects, there was a retraction of policies of teacher training, being diluted in different training space.